Electrolysed reduced water decreases reactive oxygen species-induced oxidative damage to skeletal muscle and improves performance in broiler chickens exposed to medium-term chronic heat stress - Azad, M. A. K.; Kikusato, M.; Idrus, Zulkifli; Toyomizu, M. (Taylor & Francis Ltd, 2013)
1. The present study was designed to achieve a reduction of reactive oxygen species (ROS)-induced oxidative damage to skeletal muscle and to improve the performance of broiler chickens exposed to chronic heat stress.